Analysis and comparison of improved concrete with the addition of different types of materials - Benel Ramírez, D. (Revista Ingeniería de Construcción, 2023)
The present analysis was developed by creating a detailed analysis of each article selected for the corroboration of the information and the subsequent comparison between them in order to encourage research of alternative methods of concrete production that will allow the reduction of pollution and will improve the quality and efficiency of concrete. The materials used were nanosilica, pozzolana, and recycled crushed brick that were subjected to laboratory studies with the goal of knowing their properties and of developing mix designs with different content percentages to have a broad study population and achieve representative results. These mix designs were used to create specimens that were tested in different periods to analyze their behavior in various situations. After testing, it was possible to determined that the addition of these materials are effective, in creating concrete of greater strength in the case with the addition of nanosilica, in the case of pozzolana, greater strength can be obtained at a reduced cost due to it being a natural material with various deposits where the material can be obtained in this country and throughout the world, and in the case of the addition of crushed brick, concrete with a similar strength to a conventional type can be obtained at a reduced cost of fabrication due to being a recycled